GRAFTING OF SOME MONOMERS ONTO CELLULOSE BY ATOM TRANSFER RADICAL POLYMERIZATION. ELECTRICAL CONDUCTIVITY AND THERMAL PROPERTIES OF RESULTING COPOLYMERS - Cankaya, Nevin; Temuz, Mehmet Mursit; Yakuphanoğlu, Fahrettin (Editura Acad Romane, 2018)
The research team grafted N-cyclohexylacrylamide (NCHA), 4-vinylpyridine (4VP), diacetone acrylamide (DAAM) and diallylamine (DA) onto pulverized cellulose by atom transfer radical polymerization (ATRP). First, cellulose chloroacetate (Cell. ClAc) was prepared as a macroinitiator by reacting chloroacetyl chloride with primary alcoholic OH groups on powder cellulose, where CuCl and 2,2'-bipyridine were utilized as transition-metal compound and ligand, respectively. The graft copolymers were characterized by FT-IR, elemental and thermal analyses, as well as with regard to their electrical conductivity and optical parameters. The thermal stability of the graft copolymers was determined by the TGA method. The results indicated that all the grafting processes decreased the initial thermal stability of the cellulose. The electrical conductivity of the graft copolymers was measured as a function of temperature, and it was found that it increased with increasing temperature. This indicates that the studied copolymers exhibit semiconducting behavior.
Keywords: polymers; cellulose; semiconductors; atom transfer radical polymerization (ATRP); thermogravimetric analysis (TGA)